Cayratia cordifolia C. Y. Wu ex C. L. Li, (Vitaceae Juss.), a new addition to the flora of Vietnam - Cuong, Nguyen The; Huyen, Duong Duc (Academia Journal of Biology, 2012)
In the flora of Vietnam, genus Cayratia Juss. has been known to comprise 12 species, 3 endemic species. Distribution of C. cordifolia C. Y. Wu ex C. L. Li has been known in China (Yunnan) but it has not been known in Vietnam. During the study specimens of Cayratia and documentations in herbaria, we have found that C. cordifolia C. Y. Wu ex C. L. Li has distributed also in Vietnam, with specimens collected in Sapa district, Laocai province. The specimens of voucher are kept in Hanoi Herbarium, Institute of Ecology and Biological resources, Hanoi (HN). This species is different to the others in genus Cayratia Juss. by the base of leaftlets cordate. This was a new species for the flora of Vietnam.